Spectrum and frequency of SLC26A4 mutations among Czech patients with early hearing loss with and without Enlarged Vestibular Aqueduct (EVA) - Pourová, Radka; Janousek, Petr; Jurovcík, Michal; Dvoráková, Marcela; Malíková, Marcela; Rasková, Dagmar; Bendová, Olga; Leonardi, Emanuela; Murgia, Alessandra; Kabelka, Zdenek; Astl, Jaromír; Seeman, Pavel (Annals of human genetics, 2010)
Mutations in SLC26A4 cause Pendred syndrome (PS) - hearing loss with goitre - or DFNB4 - non-syndromic hearing loss (NSHL) with inner ear abnormalities such as Enlarged Vestibular Aqueduct (EVA) or Mondini Dysplasia (MD). We tested 303 unrelated Czech patients with early hearing loss (298 with NSHL and 5 with PS), all GJB2-negative, for SLC26A4 mutations and evaluated their clinical and radiological phenotype. Among 115 available HRCT/MRI scans we detected three MD (2.6%), three Mondini-like affections (2.6%), 16 EVA (13 bilateral - 19.2% and 15.6% respectively) and 61 EVA/MD-negative scans (73.4%). We found mutation(s) in 26 patients (8.6%) and biallelic mutations in eight patients (2.7%) out of 303 tested. In 18 of 26 (69%) patients, no second mutation could be detected even using MLPA. The spectrum of SLC26A4 mutations in Czech patients is broad without any prevalent mutation. We detected 21 different mutations (four novel). The most frequent mutations were p.Val138Phe and p.Leu445Trp (18% and 8.9% of pathogenic alleles respectively). Among 13 patients with bilateral EVA, six patients (50%) carry biallelic mutations. In EVA -negative patients no biallelic mutations were found but 4.9% had monoallelic mutations. SLC26A4 mutations are present mostly in patients with EVA/MD and/or progressive HL and those with affected siblings.
Keywords: mutace; Phenotype; Prevalence; Hearing Loss, Sensorineural; Membrane Transport Proteins; Connexin 26; Vestibular Aqueduct; membránové transportní proteiny; lidé; transportéry síranu; Mutation; Sulfate Transporters; prevalence; Czech Republic; Česká republika; Syndrome; konexiny; fenotyp; aquaeductus vestibularis; percepční nedoslýchavost; Connexins; konexin 26; syndrom; Humans